The Right to a Quality Education for All in Latin American and the Caribbean - OREALC/UNESCO Santiago (Universidad Autónoma de Madrid, 2018)
This article describes the proposal of the Regional Office of Education of UNESCO for Latin America and the Caribbean (OREALC/UNESCO Santiago) about the dimensions that conform an Education of Quality from an approach of Human Rights.  The proposal analyzes, in first term, the main problems that face Latin America and the Caribbean to take ahead a process of sustainable human development and to reach the Objectives of Development of the Millenium: the overcoming of the poverty, the combat to the social inequalities, the overcoming of the sociocultural fragmentation and the violence, and the consolidation of a democratic culture. In second term it approaches the reflection of the idea of the Education like a Fundamental Human Right. From that approach and in coherence with the same one it displays a concept of quality of the education with five dimensions: equity, relevance, pertinency, effectiveness and efficiency.